Influence of Source Credibility on Agricultural Water Use Communication - Alexa J. Lamm; Courtney T. Owens; Ricky Telg; Kevan W. Lamm (Journal of Applied Communications, 2016)
As the agriculture industry strives to communicate with the public about its role in protecting natural resources such as water, it struggles to provide messages from sources the public trusts. The purpose of this quasi-experimental study explored public perception of agricultural water use and how perception was influenced by a video message delivered from four different sources including 1) an environmental scientist from the Nature Conservancy, 2) a farmer, 3) a regulator from a Florida water management district, and 4) a water scientist from the University of Florida. The findings revealed that overall the general public had a positive view of how the agriculture industry used water, regardless of message source. Differences between groups were evident when message source expertise and trustworthiness was dependent on domain area. Results indicated the respondents receiving the Nature Conservancy video treatment exhibited a significantly higher level of agreement with negatively framed items related to agriculture’s relationship with the natural environment than the respondents receiving the farmer video treatment. Based on the findings from this study, agricultural communicators should consider the trustworthiness and perceived expertise of sources, such as representatives from regulatory agencies, educational institutions, members of the agriculture sector, or environmental organizations, when developing messages about water use targeted at the general public.
Keywords: Agriculture; Messaging; Source Credibility; Video; Water